Analysis of judicial demands in health at the Regional Health Department XII (Research, Society and Development, 2017)
The management of lawsuits in health represents a challenge for most Brazilian municipalities. Many papers described in the literature characterized properly the problem as well as discussed the repercussions on the Unified Health System.In this context, the objective of this study was to analyze the situation of health judicial processes at the twelfth Regional Department in Registro, São Paulo´s state, evaluating the profile of the users who claim in court the couverage of treatment´s costs as well as examination, procedure or medication. For this, we analyzed data on lawsuits in the health field at the twelfth Regional Department in Registro (SP) from january 2009 to october 2015.The variables studied were gender, age, municipality of origin of the lawsuit, the mentioned disease, the medical prescription origin, specialty of the prescriber, type of lawsuit triggered, year of the lawsuit, entity judicially triggered and requested items. It was analyzed thirty-eight lawsuits against the twelfth Regional Department, it was observed the prevalence of the female gender, age group above 51 years and originating from the municipality of Registro (SP).The most of the judicial actions are for care given at the Unified Health System, by prescribers of specialty in Clinical Medicine and diagnosed with Diabetes Mellitus. The processes were characterized in the majority by judicial actions called Ordinary Rite, against the State. On the analyzed cases, 92% requested only medications and of these 11% supplements like vitamins and enteral diets.The number of patients who have been served through legal actions in the last three years reached 47% of the total cases registered during the period of the seven years analyzed and the approximate cost was R$ 1,340,000.00.This study contributes to the diagnosis of the processes related to the health judicialization in the region studied. The results showed a predominance of processes which comes from of patients with Diabetes Mellitus which reinforces the emergency needs to discuss public policies able to attend the needs and demands of the community based in the changes generated by the increase of chronic diseases.